State and Local Prosecution and Civil Attorney Systems, 1976 ([Verlag nicht ermittelbar], 1984)
The purpose of this data collection was to establish a current name and address listing of state and local government prosecution and civil attorney agencies and to obtain information about agency function, jurisdiction, employment, funding, and attorney compensation arrangements. The data for each agency include information for any identifiable local police prosecutors. Excluded from the study were private law firms that perform legal services periodically for a government and are compensated by retainers and fees. Variables cover agency functions and jurisdiction, agency funding, number and types of employees, compensation and employment restrictions for attorneys, agency's geographical jurisdiction, number of branch offices, and number of branch office employees.